Petrology of continental, OIB-like, basaltic volcanism in Saudi Arabia: Constraints on Cenozoic anorogenic mafic magmatism in the Arabian Shield - Ali, Shehata; Abdallah, Shehta E.; Abu Anbar, Mohamed M.; Azzaz, Sayed A.; Alrashidi, Khuloud N. (Frontiers in Earth Science, 2022)
Continental basaltic volcanism in the Arabian Shield of Saudi Arabia has distinctive mineralogical and geochemical features important for understanding the composition of their mantle source and melting conditions. The studied Cenozoic basaltic rocks (19.3–15 Ma) occur at Jabal Al Gharib and Jabal Al Ghuraybayn areas within Al Qasr quadrangle and southwest of Hail City in Saudi Arabia. They show similar chondrite normalized REE patterns, suggesting that they were derived from a common mantle source. Their OIB-like features, silica undersaturated nature, and incompatible trace element ratios all reveal asthenospheric mantle source and argue against crustal contamination process, subduction contribution, and interaction with lithospheric mantle. Moreover, the elevated compatible trace element concentrations of Ni, Cr and Co and the low and relatively narrow range of FeOtotal/MgO ratios argue for their nearly primitive nature and indicate that the role of crystal fractionation processes was minor during the evolution of the studied rocks. The estimated temperatures indicate that the sequence of crystallization likely began with olivine at 1378–1475 ℃, then clinopyroxene at 1137–1214 ℃, and soon after followed by plagioclase at 1096–1108 ℃. Plagioclase geo-hygrometer reveal 0.63–1.41 wt.% water contents, suggesting crystallization under hydrous condition. The basalts have geochemical features such as high (K2O+Na2O)/TiO2, Zr/Hf, and Nb/Ta ratios and negative K anomalies which suggest carbonated peridotite mantle source. Their bulk-rock compositions are consistent with < 5% CO2 in their peridotite melts. Highly incompatible elemental ratios supported by REE modeling indicate that they were generated by low degrees (4–10 %) of partial melting of a garnet–bearing lherzolite mantle source. The garnet signature in the source region suggests a deeper origin exceeding ~ 85 km. The basanite compositions fall within the range of alkaline OIB, and intracontinental basalts formed in rifted region. Moreover, they show geochemical characteristics typical of Cenozoic rift-related Oman basanites and other Arabian intraplate volcanic rocks. The basaltic volcanism in Saudi Arabia seems to be the result of melting asthenospheric mantle source in response to the lithospheric extension that spatially and temporally linked to Red Sea rifting and triggered anorogenic mafic magmatism due to passive mantle upwelling beneath the Arabian Shield.